Rooting of Bacuri stem cuttings (Platonia insignis Mart.) treated with Indolbutyric Acid (AIB) (Research, Society and Development, 2020)
Bacurizeiro (Platonia insignis Mart.) It is a species native to Africa, derived from the extraction of statistics from the Northeast of Pará and great regional interest. The experiment was carried out in a causalized open block design. Woody and semi-woody and standardized stem cuttings were collected, 15 cm long and 8 mm in diameter, without leaves, with horizontal cut without bevel and bevel at the base in the dosages. As they were treated with two AIB concentrations (3000 and 6000 mg L-1), in addition to the control where it used water. After the procedures, cuttings were buried at 2/3 of their length in an upright position. The cuttings were moistened daily, for 120 days, and those that were tested every 30 days. The following variables were evaluated: Average percentage of sprouts (PEST), average percentage of bud sprouts (PGB) and average number of roots (NR). As semi-hardwood cuttings are more indicated in relation to woody to be used in the propagation process of bacurizeiros. Rooting via propagation of cuttings occurred in greater proportion in the semi-hardwood branches and at the dosage of 6000 mg of L-¹, however the dosage of 3000 mg of L-¹ has already favored or rooted. Thus, the better the capacity to absorb water, nutrients, quantity of reserves, more balanced hormonal balance and, consequently, greater production of bacurizeiro. The objective of this work was to verify the potential of triggering cuttings caused by bacuri (woody and semi-hardwood) treated with different dosages of IBA (3000 and 6000 mg L-1) in addition to the control.